U.S. Figure Skating qualifying competition structure: Identify. Develop. Promote (The Professional Skater PS Magazine, 2019)
The new competitive pipeline features the following: 1. A National Qualifying Series (NQS) 2. New names for qualifying oompetitions 3. A National High-Performance Developrnent Team Camp 4. Additional singles athletes qualifying for sectional competition 5. A new, earlier pathway for pairs and dance teams.